LEGAL PROTECTION FOR VICTIMS IN CORPORATE CRIME FROM THE PERSPECTIVE OF JUSTICE - Maryana, Eny; Asmariah, Asmariah (International Journal of Social and Management Studies, 2023)
Corporate crimes often result in significant losses to society and victims. Therefore, an ideal regulatory direction is needed to ensure adequate legal protection for victims of corporate crimes in Indonesia. The ideal regulation is by implementing a cumulative punishment system for corporate crime perpetrators according to the Criminal Code, which is a cumulative sanction in the provision of two equal sanctions that add up or stack up in accordance with Article 14c paragraph (1), Article 14a, and Article 14b which contain the understanding that the law (as a cumulative policy) and/or Criminal Code Article 100 regarding the death penalty as an alternative route to maximizing criminal sanctions against corporations. This is intended to achieve justice for the victims and create a deterrent effect for perpetrators. The problem that often arises is the difficulty in upholding justice in the enforcement process of corporate crimes. The numerous cases of corporate perpetrators escaping legal action prove that legal protection for victims in Indonesia is still far from the principle of justice. This study aims to analyze the ideal regulatory direction to realize legal protection for victims of corporate crimes from the perspective of justice. This study uses a descriptive-analytical approach with a normative juridical method and examines legislation and court decisions related to corporate crimes. The results show that legal protection for victims of corporate crimes is still inadequate, especially in terms of receiving criminal sanctions in the form of imprisonment or compensation. In addition, law enforcement processes are often hindered by the economic and political power of corporations, which can influence the course of legal proceedings. This creates injustice for victims who feel they are not being treated fairly in the legal decision-making process. Therefore, an ideal regulatory direction is necessary to ensure that victims receive adequate legal protection and balanced justice.